Hand hygiene after the COVID-19 pandemic: Is it still at a high level? - Jinqi Wang; Yaofei Liu; Neng Li; Yifen Zhu; Min Du; Xiaoman He (PLoS ONE, 2025)
Background Hand hygiene (HH) is crucial for preventing healthcare-associated infections (HAIs), with compliance notably increasing during the COVID-19 pandemic. Whether this adherence can be sustained remains uncertain. We sought to assess changes in HH compliance following the pandemic and explore its correlation with HAIs. Methods A longitudinal study was launched to assess HH compliance and HAIs across two phases. Phase 1 spanned from October 2021 to January 2023, a period of normalized prevention and control of COVID-19, while phase 2 extended from February 2023 to July 2024, following the downgrade in the management of COVID-19. Observers recorded HH practices. HAIs were identified through using semi-automated, continuous surveillance software. Pearson correlation coefficient (rs) was used to evaluate the relationship between HAIs and HH. Results A total of 2,233 HH opportunities were observed with 966 during Phase 1 and 1,267 in Phase 2. Compliance with HH significantly declined from 90.27% (95% CI: 85.34% to 95.4%) in Phase 1 to 82.56% (95% CI: 80.35% to 84.61%) in Phase 2 (P < 0.001). Concurrently, the incidence of HAI rose notably from 16.79‰ (95% CI: 16.20‰ to 17.39‰) to 18.71‰ (95% CI: 18.20‰ to 19.24‰) (P < 0.001). However, despite these concurrent trends, monthly analysis found no statistically significant correlation between HH compliance and HAI incidence (rs = −0.296; P = 0.0897). Conclusions As the pandemic threat waned, maintaining high HH compliance became challenging, indicating it’s time to implement additional strategies. Moreover, the correlation between HH and HAI requires further study to uncover.